HGF-Modified Dental Pulp Stem Cells Mitigate the Inflammatory and Fibrotic Responses in Paraquat-Induced Acute Respiratory Distress Syndrome - Panpan Geng; Yuning Zhang; Huan Zhang; Xiwen Dong; Yuefeng Yang; XiaoNa Zhu; Chu-Tse Wu; Hua Wang (Stem Cells International)
Paraquat (PQ) poisoning can cause acute lung injury and progress to pulmonary fibrosis and eventually death without effective therapy. Mesenchymal stem cells (MSCs) and hepatocyte growth factor (HGF) have been shown to partially reverse this damage. MSCs can be derived from bone marrow (BM-MSCs), adipose tissue (AD-MSCs), umbilical cord (UC-MSCs), dental pulp (DPSCs), and other sources. The biological characteristics of MSCs are specific to the tissue source. To develop an effective treatment for PQ poisoning, we compared the anti-inflammatory and antifibrotic effects of UC-MSCs and DPSCs and chose and modified a suitable source with HGF to investigate their therapeutic effects in vitro and in vivo. In this study, MSCs’ supernatant was beneficial to the viability and proliferation of human lung epithelial cell BEAS-2B. Inflammatory and fibrosis-related cytokines were analyzed by real-time PCR. The results showed that MSCs’ supernatant could suppress the expression of proinflammatory and profibrotic cytokines and increase the expression of anti-inflammatory and antifibrotic cytokines in BEAS-2B cells and human pulmonary fibroblast MRC-5. Extracellular vesicles (EVs) derived from MSCs performed more effectively than MSCs’ supernatant. The effect of DPSCs was stronger than that of UC-MSCs and was further strengthened by HGF modification. PQ-poisoned mice were established, and UC-MSCs, DPSCs, and DPSCs-HGF were administered. Histopathological assessments revealed that DPSCs-HGF mitigated lung inflammation and collagen accumulation more effectively than the other treatments. DPSCs-HGF reduced lung permeability and increased the survival rate of PQ mice from 20% to 50%. Taken together, these results indicated that DPSCs can suppress inflammation and fibrosis in human lung cells better than UC-MSCs. The anti-inflammatory and antifibrotic effects were significantly enhanced by HGF modification. DPSCs-HGF ameliorated pulmonitis and pulmonary fibrosis in PQ mice, effectively improving the survival rate, which might be mediated by paracrine mechanisms. The results suggested that DPSCs-HGF transplantation was a potential therapeutic approach for PQ poisoning.